AN ANALYSIS OF ERROR IN PRONOUNCING DENTAL FRICATIVE SOUNDS BY THE FIRST YEAR STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM - Putri Yulianti; Ferry Rita; Zarkiani Hasyim (e-Journal of ELTS (English Language Teaching Society), 2021)
This research was aimed to obtain the most problematic dental fricative sounds to pronounce and to determine the factor caused by the students to produce error in pronouncing dental fricative sounds. The researchers applied descriptive qualitative design by purposive sampling technique to choose the participants. There were 15 participants taken from the first-year students of English Education Study Program 2020/2021. The instruments of data collection were documents and interview. The document is in the form of video speaking from the participant, used to analyze students pronunciation and the interview used to decide the factor of students error. The result of the research showed that the frequency of students error were 15 percent in /θ/ sound and 85 percent in /ð/ sound. Most of the students substituted sound /θ/ with /t/ and sound /ð/ with /d/. They made the error because they have interference from their mother tongue. Thus, the most problematic dental fricative sound is /ð/ sound and the error caused by the students is interlingual error.